P01.063 Influence of Pregnancy on Glioma Patients. (19th September 2018) - Forster, M; Baumgarten, P; Gessler, F; Maurer, G; Senft, C; Hattingen, E; Seifert, V; Harter, P; Franz, K
Abstract: Background: Data about the influence of pregnancy on progression free survival and overall survival of glioma patients are sparse and controversial. We aimed at providing further evidence on this relation. Material and Methods: The course of 18 glioma patients giving birth to 23 children after tumor surgery was reviewed. Results were compared to the course of 18 nulliparous female patients matched for tumor diagnosis including molecular markers, extent of resection and tumor location. Results: Tumor pathology was astrocytoma in 9 patients, oligodendroglioma in 6 patients and ependymoma in 3 patients. Time interval between tumor resection and delivery was 5.3 ± 4.4 years, and all newborns were healthy after uneventful deliveries. Tumor progression was diagnosed during pregnancy in 1 patient, and 4 patients displayed progressive disease 31.0 ± 11 months after delivery. Three of these patients underwent second surgery after delivery, whereas resection of recurrent tumor was performed in two women before pregnancy. Among nulliparous patients 9 women suffered from tumor progression, resulting in re-operation in 7 patients and/or further adjuvant treatment in 6 cases. Progression-free survival did not differ between patients with children and patients without children (6.0 ± 4.2 vs. 7.5 ± 3.2 years; p=0.4). Moreover, in both groups, median overall survival was not reached after a mean follow-up period of 9.7 ± 5.7 years in glioma patients who gave birth to a child and 8.9 ± 4.2 years in nulliparous glioma patients. Conclusion: Pregnancy has neither a positive nor a negative influence on the clinical course of glioma patients. Likewise, glioma has no impact on delivered children's health.